Pengembangan Website Cybercounseling Realita untuk Meningkatkan Keterbukaan Diri Siswa Sekolah Menengah Kejuruan - Prabawa, Abi Fa'izzarahman; Ramli, M; Fauzan, Lutfi (Jurnal Kajian Bimbingan dan Konseling, 2018)
This research and development aims to produce a cybercounseling reality website and a reality cybercounseling guidebook to improve self-disclosure for Vocational High School students which are grateful theoretically and practically. The research and development study steps are: preliminary study, product development, and product test. Product’s guidelines are tested using one group pretest-posttest design. Product test results show that cybercounseling reality website is gratefully theoretically and practically and also effectively to improve Vocational High School students’ self-disclosure.